Mega‐Regional Agreements and the Struggle for Economic Order in the Asia‐Pacific Region. Issue 4 (27th December 2018) - Novikov, Dmitry; Shumkova, Veronika
Abstract : The U.S. withdrawal from the Trans‐Pacific Partnership (TPP) project in January 2017 effectively marked the end (at least—for some time) of the period of active competition between so‐called "mega‐regional agreements" in the Asia‐Pacific region. A flagship of the Obama administration's initiatives in Asia, the TPP spurred China to intensify work on an alternative project—its Regional Comprehensive Economic Partnership (RCEP)—and sparked an unusual wave of competition among APR institutions. Significantly, Russia joined this "partnership race" in 2016, putting forward an initiative to build a Greater Eurasian Partnership. It became something of a given that any power aspiring to regional leadership must have its own "partnership plan" to promote. At the same time, the formation and development of mega‐regional partnerships is an important stage in the regionalization of the world economy and global politics and a key element of the new phenomenon of regionalization. This article examines the TPP and RCEP initiatives as attempts to form a regional international order holding some degree of autonomy from the global set of rules for the functioning of regional international systems—in this case, that of the APR.